Identification of a novel nonsense mutation and a recurrent missense mutation in UROS gene in a patient with congenital erythropoietic porphyria - Jia, Ning; Yimin, Yusupu; Li, Ming; Jiang, Long; Liu, Yeqiang (Frontiers in Genetics, 2025)
Background: Congenital erythropoietic porphyria (CEP, OMIM #263700) is a rare autosomal recessive disease characterized by skin photosensitivity, hypertrichosis, scarring in light-exposed areas, erythrodontia, and dark-reddish urine. The severity of the clinical phenotype is directly associated with the complete loss of enzymatic activity resulting from UROS mutations.Methods: To understand the genetic etiology of CEP in a 9-year-old female proband, we checked clinical data and collected peripheral blood samples from her and her parents. Genomic DNA was isolated and subjected to polymerase chain reaction (PCR) amplification. Sanger sequencing was performed to detect potential mutations. Bioinformatics analysis was performed to assess the pathogenicity of the identified variant, and 3D protein modeling was conducted to predict its impact on protein structure.Results: The proband presents with red wine-colored urine in early infancy, reddish-brown, notched incisors, and vellus hair on the forehead and trunk. Blisters develop on sun-exposed areas, leaving hyperpigmented macules after rupture. Sanger sequencing identified a previously reported missense mutation (c 0.425C > T: p.P142L) and a novel nonsense mutation in the UROS gene (c 0.325A > T: p.K109*). Bioinformatic analysis indicated that the c 0.325A > T: p.K109* variant is pathogenic. Structural modeling demonstrated that the heterozygous c.325A > T transversion in exon 6 of UROS caused a K109 termination at the protein’s α6 helix chain.Conclusion: Our findings underscored the critical role of Sanger sequencing in the accurate diagnosis of atypical CEP cases and in facilitating informed genetic counseling. The identification of a UROS gene novel mutation in this case indicates a mild phenotype, further expanding the spectrum of disorders associated with UROS variants.